(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
This paper presents a numerical study of heat transfer of a fully developed turbulent flow inside elliptical tube with different aspect ratio of constant surface area, by using (AL2O3-water) nanofluid with average nanoparticles diameter (20 nm). Multi-phase mixture model has been used to calculate the Nusselt number, nanofluid velocity, and pressure drop. “The three-dimensional Navier-Stokes”, energy, and volume fraction equations are solved by ANSYS fluent with “finite volume method (FVM)”. The numerical results show reasonable acceptance with error bounds approximately to (10.34%) upon pervious experimental works. It is found that the increase in nanoparticles “volume concentration (φ)” will increase the Nusselt number with little “pressure drop” rise. The elliptical tube with 0.25 aspect ratio gives best enhancement in heat transfer compared with circular tube with maximum Nusselt number (52.9%) and nanofluid volume concentration of 1.5%, but it is less effective in the process of transporting fluids to distance due to the high pressure drops between entry and exit of fluid compared to tube with circular sections within a certain range of Reynolds number (3000-9240).